2023
DOI: 10.1001/jamaophthalmol.2022.5237
|View full text |Cite
|
Sign up to set email alerts
|

Inequities and Research Gaps in Ophthalmology

Abstract: ImportanceDeficient ophthalmologic care is costly to patients, making the identification of groups not receiving adequate care of vital importance. The current landscape of equity in ophthalmic care has yet to be thoroughly investigated and is important to ensure inclusivity and patient-centered care.ObjectiveTo perform a scoping review of the literature pertaining to health care inequities in the field of ophthalmology.Evidence ReviewA comprehensive database search using MEDLINE (via PubMed) and Ovid Embase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…The Basic and Clinical Science Course, long considered a cornerstone of ophthalmology resident education, has recently added a new chapter dedicated entirely to social determinants of health, ensuring that our future workforce will be well versed in these issues and propelled to work to address them. These efforts will drive further attention and research into reducing ophthalmologic health disparities to augment the 75 articles identified by Hemmerich et al 1 and fill in gaps in our knowledge of these inequities. This research will be invaluable in guiding future initiatives to ensure that high-quality ophthalmology care is available for all patients regardless of their identity.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…The Basic and Clinical Science Course, long considered a cornerstone of ophthalmology resident education, has recently added a new chapter dedicated entirely to social determinants of health, ensuring that our future workforce will be well versed in these issues and propelled to work to address them. These efforts will drive further attention and research into reducing ophthalmologic health disparities to augment the 75 articles identified by Hemmerich et al 1 and fill in gaps in our knowledge of these inequities. This research will be invaluable in guiding future initiatives to ensure that high-quality ophthalmology care is available for all patients regardless of their identity.…”
mentioning
confidence: 93%
“…However, research is not enough. Many medical and ophthalmology societies have developed active initiatives seeking to address the issues raised in the articles cited by Hemmerich et al 1 For the American Medical Association (AMA), health equity has become one of its highest priorities. In 2019, the AMA created its Center for Health Equity, to embed a commitment to health equity in all aspects of AMA's work and mission.…”
mentioning
confidence: 99%
See 3 more Smart Citations